Enhancing academic reading skills through extensive reading. Issue 1 (2nd January 2017) - Nhapulo, Marcos Abilio; Simon, Ellen; Van Herreweghe, Mieke
Abstract: The current study explores the feasibility of an extensive reading programme in the context of a low-income country (Mozambique), as well as the influence of extensive reading on academic reading. The programme took over 4 months and was conducted among 30 students majoring in Journalism at the Eduardo Mondlane University in Mozambique in 2013. The study applied a reading comprehension pre-test and post-test design, as well as three-minute reading speed pre- and post-tests. Using SPSS statistical analysis, three paired-samples t -tests were administered and the progress from the reading speed pre-test to the post-test was found to be significant. Study results indicate that reading speed and reading comprehension are complementary abilities, since students who achieved higher reading speed also scored higher marks in the academic reading comprehension tests. Moreover, the reading comprehension results showed that extensive general reading transfers to academic reading skills. However, students' motivation to read did not show a considerable improvement. It can be concluded that an extensive reading programme is indeed feasible and desirable among Mozambican university students, but that there are still problems concerning requirements for the implementation of such extensive reading programmes.